Prognostic Role of Anemia in COVID-19 Patients: A Meta-Analysis - Marco Zuin; Gianluca Rigatelli; Laura Quadretti; Luisella Fogato; Giovanni Zuliani; Loris Roncon (MDPI AG, 2021)
Introduction. The prevalence and prognostic implications of anemia in patients infected by the SARS-CoV-2 remains unclear. We performed a systematic review and meta-analysis to assess the prevalence and mortality risk in COVID-19 patients with anemia. Methods. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed in abstracting data and assessing validity. We searched MEDLINE and Scopus to locate all the articles published up to 1 September 2021, reporting data on the adjusted OR (aOR) for mortality among COVID-19 patients with anemia. The pooled prevalence of anemia among COVID-19 patients was calculated using a random effects model and presenting the related 95% confidence interval (CI), while the mortality risk was estimated using the Mantel-Haenszel random effects models with odds ratio (aOR) and related 95% CI. Statistical heterogeneity was measured using the Higgins I2 statistic. Results. Five studies, enrolling 9.623 COVID-19 patients [3.707 males (38.5%)], met the inclusion criteria and were included in the final analysis. The pooled prevalence of anemia was 25.6% of cases (95% CI: 8.3-56.5%), with high heterogeneity (I2 = 98.9%). Meta-regression showed that the anemia prevalence was influenced by a direct correlation with age (p = 0.007) and chronic kidney disease (p = 0.004) as moderating variables. Conversely, an inverse relationship was observed with male gender (p < 0.0001). Anemia was significantly associated with higher risk of short-term mortality (aOR: 1.69, 95% CI: 1.28-2.24, p < 0.001), with low heterogeneity (I2 = 0%). Conclusions. Anemia represents a major comorbidity in about 25% of COVID-19 patients and it is associated with about 70% higher risk of short-term mortality.